The Role of Full Day School Learning in Forming Student Character at the Integrated Islamic Elementary School (IT) Fatima Azzahra Cimanggung - Siti Nurhalimah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Character is very important andIfundamental. Given theimportance of a character, then education has the responsibility to instill it through the process of learning in school. Full day study program or often called full day school is an effort made by educational institutions to instill character. All that is done to keep learners of moral decline. The formulation of the problem of this research is: 1) How the practice of full day school learning in the formation of student characters in SD ITFathumah Azzahra. 2) How to role of learning full day school in the formation of student characters in SD IT Fathumah Azzahra Cimanggung. This study aims: 1) To describe the practice of full day school learning in the character formation of students in SD IT Fathumah Azzahra Cimanggung. 2). To know the role of full day school learning in the formation of student character in SD IT Fathumah Azzahra Cimanggung. The research model used is field research and qualitative lapproach, with research subjects are students, teachers and principals. Data collection methods used were interviews, observation and documentation. Based on this research, it can be concluded that: 1) Practice of full day school learning in SD IT Fathumah Azzahra Cimanggung that is First, learning is done from 07.15-14.00. Second, use five effective days. Third, fun learning 2) Full day school can shape the character of students are: religious, honest, discipline, creative, independent, spirit, love homeland, friendly, social care, and responsibility. Student character is formed through full day learning activities from morning until afternoon at school.